Effect of 2.4 GHz WiFi Frequency Electromagnetic Wave Radiation on Green Bean’s Growth (Journal of Basic and Applied Research in Biomedicine, 2022)
In this research, access points are placed near the green bean’s seed to identify the effect of 2.4 GHz electromagnetic waves to green bean’s growth. There are 3 groups of green bean’s seed, one is positioned near one access point, another is positioned near two access points, and the last is positioned near 3 access points. For the control treatment, another sample group is placed in area without WiFi access, with 30cm distance and 6 x 24 hours times elapsed. The result shows that samples with 63 mV/m electric field strength that comes from 3 WiFi access points could grow till 8.6 cm, the samples with two access points with its electric field strength 63V/m could grow until 8.8 cm, and samples with one Wi-Fi access point with electric field strength of 0.792 mV/m could grow until 9 cm. As for the controlling samples, it could grow until 9.5 cm. From the result, we can conclude that samples will grow slower when they are affected by the electromagnetic wave radiation. We assumed that the radiation of 2.4 GHz electromagnetic waves disturb the performance of the green bean’s growth.